1996
DOI: 10.1021/bi9518048
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Multicatalytic Endopeptidase by Oxidants. Effects on Enzyme Structure

Abstract: It is well established that the functional properties of proteins can be compromised by oxidative damage and, in vivo, proteins modified by oxidants are rapidly degraded. It was hypothesized that oxidants may also affect the ability of proteases to hydrolyze peptides and proteins. We therefore examined the effect of oxidants on the endopeptidase activities of the 650 kDa 20S proteasome or multicatalytic endopeptidase (MCP), which is thought to play a central role in nonlysosomal protein breakdown. Treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
33
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 28 publications
7
33
0
Order By: Relevance
“…On the other hand, further oxidation of already oxidized proteasome (i.e. T24-starved proteasome) resulted in partial inactivation of the three peptidic activities (Table V), as observed for proteasomes treated with increasing H 2 O 2 concentrations (Strack et al, 1996;Conconi et al, 1998;Reinheckel et al, 1998), and in a strong increase in carbonyl residues (Fig. 6).…”
Section: Modifications Of 20s Proteasome In Carbon-starved Tissuesmentioning
confidence: 52%
See 2 more Smart Citations
“…On the other hand, further oxidation of already oxidized proteasome (i.e. T24-starved proteasome) resulted in partial inactivation of the three peptidic activities (Table V), as observed for proteasomes treated with increasing H 2 O 2 concentrations (Strack et al, 1996;Conconi et al, 1998;Reinheckel et al, 1998), and in a strong increase in carbonyl residues (Fig. 6).…”
Section: Modifications Of 20s Proteasome In Carbon-starved Tissuesmentioning
confidence: 52%
“…Conflicting results have been reported about the chymotrypsin-like activity of 20S proteasome, which was found to be either activated (Strack et al, 1996) or not (Reinheckel et al, 1998) by in vitro oxidative treatment. It has been hypothesized that the activation by H 2 O 2 found by Strack et al (1996) was mediated via an interaction of the proteasome and the PA28 activator (Reinheckel et al, 1998). However, without excluding a possible interaction between the 20S proteasome and the PA28 activator in vivo, our data show that the purified proteasome may be activated by a mild oxidation treatment only, i.e.…”
Section: Modifications Of 20s Proteasome In Carbon-starved Tissuesmentioning
confidence: 91%
See 1 more Smart Citation
“…H 2 O 2 has also been implicated in the induction of NF⑂B translocation by oxidized LDL in monocytes (11,12). In earlier work, we demonstrated that hydroxyl radicals (OH⅐) but not H 2 O 2 or superoxide is involved in phorbol ester-induced monocytic differentiation of HL-60 cells (13).…”
mentioning
confidence: 80%
“…Proteasome activity is under the regulation of several factors and conditions among which oxidative stress plays a dual role: sustained oxidative insult is reported to inactivate proteasome by direct oxidation or by the formation of protein cross-linking and aggregates (34); but on the other hand exposure to mild oxidative injury has been demonstrated to stimulate proteasome activity, presumably through favoring conformation changes in the 20S proteasome complex (35,36). Accordingly, in our FALS model, where a mild oxidative stress is operative, an activation of proteasome was found in response to G93A Cu,Zn SOD expression in order to counteract ROS toxicity via degradation of oxidized proteins.…”
Section: Involvement Of Proteasome In Neurodegenerationmentioning
confidence: 99%